An enlightening procedure to explain the extreme power of synchrotron radiation - Margaritondo, Giorgio (Journal of synchrotron radiation, 2019)
A simple approach exploits quantum properties to justify the dependence on γ4 of the total synchrotron emitted power. It also clarifies some apparent puzzles and brings to light the underlying, multiple relativistic phenomena